Paths and detours in the trajectory of the Brazilian psychiatric reform - Sade, Rossana Maria Seabra [UNESP]; Sashidharan, Sashi P.; Silva, Maria De Nazareth Rodrigues Malcher De Oliveira (Universidad Nacional de Lanus, 2021)
This article looks at the principles and guidelines of the Unified Health System as well as the current situation and the limitations and possibilities of Brazilian mental health policy. Based on a review of national and international government documents and the scientific literature from 2015-2020, the study observed positive advances in mental health. However, the psychiatric reform has experienced setbacks, and the balance of mental health care has swung towards hospital-centered treatment. These changes have impeded the implementation of the Psychosocial Care Network, as well as the development of therapeutic practices and strategies focused on the person’s experience, their daily life and their relations with the health promotion network. By questioning the supremacy of medical-psychiatric knowledge in the treatment of “mental illness” in the public health care system, the psychiatric reform cleared a path for the construction of new ways of addressing psychological suffering. These gains are currently at risk, making a wider debate on the current trends in mental health care in Brazil essential.
Caminos y desvíos en la trayectoria de la reforma psiquiátrica brasileña
Keywords: Brasil; Brazil; Deinstitutionalization; Desinstitucionalización; Mental Health; Mental Health Services; Psychiatric Reform; Salud Mental; Servicios de Salud Mental; Sistema Único de Salud; Unified Health System